Answer:
![Kp=3.07x10^6](https://tex.z-dn.net/?f=Kp%3D3.07x10%5E6)
Explanation:
Hello,
In this case, by knowing the given reference reactions, one could rearrange them as follows:
![2 NO(g) \leftrightarrow N_2(g) + O_2(g); Kp_2 = \frac{1}{2.3 x 10^{-19}}=4.35x10^{18}](https://tex.z-dn.net/?f=2%20NO%28g%29%20%5Cleftrightarrow%20N_2%28g%29%20%2B%20O_2%28g%29%3B%20Kp_2%20%3D%20%5Cfrac%7B1%7D%7B2.3%20x%2010%5E%7B-19%7D%7D%3D4.35x10%5E%7B18%7D)
![N_2(g) + 2O_2(g) \leftrightarrow 2NO_2(g);Kp_3=(8.4x10^{-7})^2=7.056x10^{-13}](https://tex.z-dn.net/?f=N_2%28g%29%20%2B%202O_2%28g%29%20%5Cleftrightarrow%202NO_2%28g%29%3BKp_3%3D%288.4x10%5E%7B-7%7D%29%5E2%3D7.056x10%5E%7B-13%7D)
Subsequently, to obtain the main reaction, we add the aforementioned reference rearranged reactions as shown below (just as reference):
![2NO(g)+N_2(g)+2O_2\leftrightarrow 2NO_2(g)+N_2+O_2](https://tex.z-dn.net/?f=2NO%28g%29%2BN_2%28g%29%2B2O_2%5Cleftrightarrow%202NO_2%28g%29%2BN_2%2BO_2)
Consequently, the equilibrium constant is computed as:
![Kp=\frac{[N_2][O_2]}{[NO]^2} * \frac{[NO_2]^2}{[N_2][O_2]^2} =Kp_2*Kp_3=4.35x10^{18}*7.056x10^{-13}=3.07x10^6](https://tex.z-dn.net/?f=Kp%3D%5Cfrac%7B%5BN_2%5D%5BO_2%5D%7D%7B%5BNO%5D%5E2%7D%20%2A%20%5Cfrac%7B%5BNO_2%5D%5E2%7D%7B%5BN_2%5D%5BO_2%5D%5E2%7D%20%3DKp_2%2AKp_3%3D4.35x10%5E%7B18%7D%2A7.056x10%5E%7B-13%7D%3D3.07x10%5E6)
Best regards.
Answer:
![r_{H_2} = \frac{-1}{2} r_{HI}](https://tex.z-dn.net/?f=r_%7BH_2%7D%20%3D%20%5Cfrac%7B-1%7D%7B2%7D%20r_%7BHI%7D)
Explanation:
Hello!
In this case, considering the given chemical reaction:
![H_2(g) + I_2(g) \rightarrow 2HI(g)](https://tex.z-dn.net/?f=H_2%28g%29%20%2B%20I_2%28g%29%20%5Crightarrow%202HI%28g%29)
Thus, by applying the law of rate proportions, we can write:
![\frac{1}{-1} r_{H_2} = \frac{1}{-1}r_{i_2} = \frac{1}{2} r_{HI}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B-1%7D%20r_%7BH_2%7D%20%3D%20%5Cfrac%7B1%7D%7B-1%7Dr_%7Bi_2%7D%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20r_%7BHI%7D)
Whereas the stoichiometric coefficients of reactants are negative due their disappearance and that of the product is positive due to its appearance. In such a way, when we relate the rate of disappearance of hydrogen gas to the rate of formation of hydrogen iodide, we obtain:
![r_{H_2} = \frac{-1}{2} r_{HI}](https://tex.z-dn.net/?f=r_%7BH_2%7D%20%3D%20%5Cfrac%7B-1%7D%7B2%7D%20r_%7BHI%7D)
Best regards!
<span>A) Frequency due to motion
As you are moving toward the object that is making the sound the frequency is higher. When you begin to move away the frequency lowers.
</span>
This are letters of the alphabet some are periods and some are commas also they do not form any words or meaning
hope this helped ;)